Friend or Foe? : Cross-Border Linkages, Contagious Banking Crises, and 'Coordinated' Macroprudential Policies - Choi, Seung; Kodres, Laura; Lu, Jing. (Washington, D.C. : International Monetary Fund, 2018)
This paper examines whether the coordinated use of macroprudential policies can help lessen the incidence of banking crises. It is well-known that rapid domestic credit growth and house price growth positively influence the chances of a banking crisis. As well, a crisis in other countries with high trade and financial linkages raises the crisis probability. However, whether such 'contagion effects' can operate to reduce crisis probabilities when highly linked countries execute macroprudential policies together has not been fully explored. A dataset documenting countries' use of macroprudential tools suggests that a 'coordinated' implementation of macroprudential policies across highly-linked countries can help to stem the risks of widespread banking crises, although this positive effect may take some time to materialize.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet